2023
DOI: 10.1227/neu.0000000000002332
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Poor-Grade Aneurysmal Subarachnoid Hemorrhage

Abstract: BACKGROUND:Poor-grade aneurysmal subarachnoid hemorrhage (aSAH) is associated with high mortality and poor disability outcome. Data on quality of life (QoL) among survivors are scarce because patients with poor-grade aSAH are underrepresented in clinical studies reporting on QoL after aSAH.OBJECTIVE:To provide prospective QoL data on survivors of poor-grade aSAH to aid clinical decision making and counseling of relatives.METHODS:The herniation World Federation of Neurosurgical Societies scale study was a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This effort will greatly aid physicians in gaining a High-grade aSAH is associated with elevated mortality and unfavorable neurologic outcomes [13]. A recent investigation revealed significant proportion of survivors of high-grade aSAH showed a good quality of life after appropriate clinical decision making [14]. Therefore, there is a critical need for early prediction of long-term functional outcomes and the identification of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This effort will greatly aid physicians in gaining a High-grade aSAH is associated with elevated mortality and unfavorable neurologic outcomes [13]. A recent investigation revealed significant proportion of survivors of high-grade aSAH showed a good quality of life after appropriate clinical decision making [14]. Therefore, there is a critical need for early prediction of long-term functional outcomes and the identification of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent data, however, suggest that despite high early mortality, patients with high-grade SAH can have outcomes that exceed expectations. 2 The care of the patient with aneurysmal SAH involves multidisciplinary teams who need to quickly make extremely challenging decisions, such as how and when to secure an aneurysm or how and when to alleviate intracranial hypertension. The recently published 2023 Guideline for the Management of Patients With Aneurysmal Subarachnoid Hemorrhage from the American Heart Association/American Stroke Association 1 not only discusses these pressing matters but, importantly, also underscores the crucial role that good medical management has on patient outcomes.…”
Section: Natural Historymentioning
confidence: 99%
“…1 Recent data, however, suggest that despite high early mortality, patients with high-grade SAH can have outcomes that exceed expectations. 2…”
Section: Natural Historymentioning
confidence: 99%
“…The results of the ANOVA indicated that the differences in the number of patients among the different midyear The discrepancy between patients assigned to poor WFNS/HH grades and a growing proportion of favorable outcomes in this group is problematic. It shows that besides improved patient care resulting in better outcomes, also the inherent weakness of these grading systems [19]. Consequently, the unconditional withdrawal of maximal therapy for WFNS and HH grade 5 aSAH patients has become increasingly unacceptable [20][21][22][23].…”
Section: Secondary Outcomesmentioning
confidence: 99%